CHARACTER BUILDING IN CROSS-CULTURAL SETTING: A Transitivity Analysis Of Two Kinds The Short Story By Amy Tan - Ferany Shaily Maulida, - (2007)
The present study explores "'Two Kinds", a short story by Amy Tan -an American-born Chinese, -within the issue relating to cross-cultural settings. It examines the character building of the main character and the author's intention in developing the character in relation to cross-cultural settings. The study used descriptive method in qualitative approach. The data were clauses in the short story containing Jing-mei's character in the form of "I" and "me" developed by the author. To figure out the representation of character building and the author's intention in this short story, the data were analyzed under Fairclough' s CDA with Transitivity as a tool of analysis. Based on findings and discussions, the study reveals that the main character seems to be developed es a girl who is forced by her mother to be a prodigy. She tends to be an individual person and experience internal conflict. The author seemingly wants to convey to the readers that the character was trapped in two different cultures, American and Chinese. In one side she has to obey what her mother wants as a fidelity to her parents as Chinese cultures taught her. On the other side, she wants to be part of the modem, liberal American society in which she could choose her life. This may represent lives of many people especially in America society where intercultural greatly happens. Hopefully, the writer hopes that this study would give a valuable benefit to enrich materials for literature teaching and inspire those who will undertake further study in related fields.